2020
DOI: 10.1016/j.scr.2020.102043
|View full text |Cite
|
Sign up to set email alerts
|

NODAL inhibition promotes differentiation of pacemaker-like cardiomyocytes from human induced pluripotent stem cells

Abstract: Directed cardiomyogenesis from human induced pluripotent stem cells (hiPSCs) has been greatly improved in the last decade but directed differentiation to pacemaking cardiomyocytes (CMs) remains incompletely understood. In this study, we demonstrated that inhibition of NODAL signaling by a specific NODAL inhibitor (SB431542) in the cardiac mesoderm differentiation stage downregulated PITX2c , a transcription factor that is known to inhibit the formation of the sinoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…It includes experimental tactics of embryoid body development (Yang et al, 2008 ) or monolayer attachment culture with specific biochemical conditioning (Laflamme et al, 2007 ). Yet, the differentiation of PSCs to cardiomyocytes mainly results in a mixture of atrial, ventricular, and nodal cells; therefore, the ultimate goal to guide the differentiation into a desired subtype and to create the biological pacemaker appears challenging ( Table 2 ) (Xu et al, 2002 ; He et al, 2003 ; Yang et al, 2008 ; Jung et al, 2012 , 2014 ; Mandel et al, 2012 ; Müller et al, 2012 ; Christoforou et al, 2013 ; Birket et al, 2015 ; Protze et al, 2016 ; Chauveau et al, 2017 ; Dorn et al, 2018 ; Zhang and Huang, 2019 ; Zhang et al, 2019a ; Yechikov et al, 2020 ).…”
Section: Approaches For the Engineering Of Biological Pacemakersmentioning
confidence: 99%
See 2 more Smart Citations
“…It includes experimental tactics of embryoid body development (Yang et al, 2008 ) or monolayer attachment culture with specific biochemical conditioning (Laflamme et al, 2007 ). Yet, the differentiation of PSCs to cardiomyocytes mainly results in a mixture of atrial, ventricular, and nodal cells; therefore, the ultimate goal to guide the differentiation into a desired subtype and to create the biological pacemaker appears challenging ( Table 2 ) (Xu et al, 2002 ; He et al, 2003 ; Yang et al, 2008 ; Jung et al, 2012 , 2014 ; Mandel et al, 2012 ; Müller et al, 2012 ; Christoforou et al, 2013 ; Birket et al, 2015 ; Protze et al, 2016 ; Chauveau et al, 2017 ; Dorn et al, 2018 ; Zhang and Huang, 2019 ; Zhang et al, 2019a ; Yechikov et al, 2020 ).…”
Section: Approaches For the Engineering Of Biological Pacemakersmentioning
confidence: 99%
“…Notably, only a few studies attempted to overcome this issue by focusing on deriving SAN-like cells from the cardiac differentiation and pacemaker specification of hiPSCs (Müller et al, 2012 ; Birket et al, 2015 ; Protze et al, 2016 ; Zhang and Huang, 2019 ; Yechikov et al, 2020 ). Calcium-activated potassium channels were demonstrated in hPSCs as a valid target to generate an enriched population of PC-like cells by conditioning with 1-ethyl-2-benzimidazolinone (1-EBIO).…”
Section: Approaches For the Engineering Of Biological Pacemakersmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of specific molecules has been shown to promote or inhibit certain cardiomyocyte subtypes in order to generate more specific disease models and drug testing platforms [ 70 ]. Studies show that the induction of appropriate mesoderm with different concentrations of small molecules to activate or inhibit certain signalling pathways specifically yields atrial, ventricular, or pacemaker-type cardiomyocytes [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Cardiomyocyte differentiation kits are now commercially available.…”
Section: Differentiation Of Established Ipsc Lines To Cardiomyocytesmentioning
confidence: 99%
“…An alternative strategy to reduce undesired cardiomyocyte subtype is direct differentiation to a specific subtype. Directed differentiation protocols that promote a higher fraction of ventricular, atrial, or pacemaking subtype have been reported [82][83][84][85][86][87][88]; however, none of the protocols could attain 100% yield of the desired subtype.…”
Section: Hipsc-derived Cardiomyocytesmentioning
confidence: 99%